KEY FACTORS FOR THE SUCCESS OF SME STARTUPS IN INDONESIA - Ahmad Jet Alamin A; Adrian K. Tarigan; Hulman Wasi Boangmanulu (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This study examines key success factors for UMKM startups in Indonesia, along with the challenges encountered during business growth. UMKM startups play a strategic role in the national economy; however, many fail due to incorrect strategies, particularly in financing and the adoption of digital technology. The research aims to identify the key factors influencing success at each stage of UMKM development, analyze related challenges and opportunities, and provide recommendations to support sustainable business growth. The growth framework consists of seven stages, from idea to maturity/scaling, where common obstacles include limited access to funding and low digital capability. The study employs a qualitative approach using a literature review and descriptive analysis. The findings indicate that success depends not only on ideas and capital, but also on motivation, networks, resilience, resource management, and the ability to recombine new ideas. The recommendations emphasize implementing digitalization strategies and improving understanding of financing options that match the UMKM growth stage.